Sodium efflux from voltage clamped squid giant axons. - Landowne, D (1977)
1. The efflux of radioactive sodium was measured from squid axons during simultaneous voltage clamp experiments such that it was possible to determine the efflux of sodium associated with a measured voltage clamp current. 2. The extra efflux of sodium associated with voltage clamp pulses increased linearly with the magnitude of the depolarization above 40 mV. A 100 mV pulse of sufficient duration to produce all of the sodium current increased the rate constant of efflux by about 10(-6). 3. Application of 100 nM tetrodotoxin eliminated the sodium current and the extra efflux of radioactive sodium. 4. Cooling the axon increased the extra efflux/voltage clamp pulse slightly with a Q10 of 1/1-1. On the same axons cooling increased the integral of the sodium current with a Q10 of 1/1-4. 5. Replacing external sodium with Tris, dextrose or Mg-mannitol reduced the extra efflux of sodium by about 50%. The inward sodium current was replaced with an outward current as expected. 6. Replacing external sodium with lithium also reduced the extra efflux by about 50% but the currents seen in lithium were slightly larger than those in sodium. 7. The effect of replacing external sodium was not voltage dependent. Cooling reduced the effect so that there was less reduction of efflux on switching to Tris ASW in the cold than in the warm. 8. The extra efflux of sodium into sodium-free ASW is approximately the same as the integral of the sodium current. Adding external sodium produces a deviation from the independence principle such that there is more exchange of sodium than predicted. Such a deviation from prediction was noted by Hodgkin & Huxley (1952c). 9. Using the equations of Hodgkin & Huxley (1952c) modified to include the deviation from independence reported in this paper and its temperature dependence, one can predict the temperature dependence of the sodium efflux associated with action potentials and obtain much better agreement than is possibly without these phenomena. 10. This deviation from independence in the sodium fluxes is the type expected from some kind of mixing and binding of sodium within the membrane phase.